Urinary ATP Levels Are Controlled by Nucleotidases Released from the Urothelium in a Regulated Manner - Alejandro Gutierrez Cruz; Mafalda S. L. Aresta Branco; Brian A. Perrino; Kenton M. Sanders; Violeta N. Mutafova-Yambolieva (Metabolites, 2022)
Adenosine 5′-triphosphate (ATP) is released in the bladder lumen during filling. Urothelial ATP is presumed to regulate bladder excitability. Urinary ATP is suggested as a urinary biomarker of bladder dysfunctions since ATP is increased in the urine of patients with overactive bladder, interstitial cystitis or bladder pain syndrome. Altered urinary ATP might also be associated with voiding dysfunctions linked to disease states associated with metabolic syndrome. Extracellular ATP levels are determined by ATP release and ATP hydrolysis by membrane-bound and soluble nucleotidases (s-NTDs). It is currently unknown whether s-NTDs regulate urinary ATP. Using etheno-ATP substrate and HPLC-FLD detection techniques, we found that s-NTDs are released in the lumen of ex vivo mouse detrusor-free bladders. Capillary immunoelectrophoresis by ProteinSimple Wes determined that intraluminal solutions (ILS) collected at the end of filling contain ENTPD3 > ENPP1 > ENPP3 ≥ ENTPD2 = NT5E = ALPL/TNAP. Activation of adenylyl cyclase with forskolin increased luminal s-NTDs release whereas the AC inhibitor SQ22536 had no effect. In contrast, forskolin reduced and SQ22536 increased s-NTDs release in the lamina propria. Adenosine enhanced s-NTDs release and accelerated ATP hydrolysis in ILS and lamina propria. Therefore, there is a regulated release of s-NTDs in the bladder lumen during filling. Aberrant release or functions of urothelial s-NTDs might cause elevated urinary ATP in conditions with abnormal bladder excitability.